2021
DOI: 10.1097/aog.0000000000004285
|View full text |Cite|
|
Sign up to set email alerts
|

Postpartum Salpingectomy Compared With Standard Tubal Ligation After Vaginal Delivery

Abstract: OBJECTIVE: To compare operative outcomes of postpartum salpingectomy and tubal ligation after vaginal delivery. METHODS: This retrospective cohort study identified patients who underwent tubal sterilization between January 1, 2009, and December 31, 2019, at a large academic hospital, using the electronic medical record. All patients who delivered vaginally and underwent tubal sterilization during their delivery admissions were included. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…A recent metaanalysis evaluating salpingectomy at the time of cesarean demonstrated similar operative times across three randomized controlled trials comparing salpingectomy to bilateral tubal ligation without significant differences in perioperative complications, length of stay, EBL, or post-partum re-admissions [26]. Additionally, two other studies retrospectively evaluated operative outcomes for the incorporation of salpingectomy in the immediate post-partum period following vaginal delivery [21,22]. Danis et al [22] compared postpartum salpingectomy to post-partum bilateral tubal ligation in a retrospective consecutive cohort, and found significantly longer operative times for those undergoing post-partum salpingectomy (71.44 min ± 5.81 vs. 59.13 min ± 16 min p = 0.003) similar to our own findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent metaanalysis evaluating salpingectomy at the time of cesarean demonstrated similar operative times across three randomized controlled trials comparing salpingectomy to bilateral tubal ligation without significant differences in perioperative complications, length of stay, EBL, or post-partum re-admissions [26]. Additionally, two other studies retrospectively evaluated operative outcomes for the incorporation of salpingectomy in the immediate post-partum period following vaginal delivery [21,22]. Danis et al [22] compared postpartum salpingectomy to post-partum bilateral tubal ligation in a retrospective consecutive cohort, and found significantly longer operative times for those undergoing post-partum salpingectomy (71.44 min ± 5.81 vs. 59.13 min ± 16 min p = 0.003) similar to our own findings.…”
Section: Discussionmentioning
confidence: 99%
“…Danis et al [22] compared postpartum salpingectomy to post-partum bilateral tubal ligation in a retrospective consecutive cohort, and found significantly longer operative times for those undergoing post-partum salpingectomy (71.44 min ± 5.81 vs. 59.13 min ± 16 min p = 0.003) similar to our own findings. Wagar et al [21] reported a shorter median operative time for post-partum salpingectomy compared to bilateral tubal ligation immediately following vaginal delivery (30)(31)(32)(33)(34)(35)(36)(37)(38) vs. 34 min [IQR 26-42], p = 032). However, 97% of post-partum salpingectomy cases utilized a bipolar electrocautery device [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations